Craniomandibular osteology of a new massopodan sauropodomorph (Dinosauria: Sauropodomorpha) from the Late Triassic (latest Norian) of Canton Aargau, Switzerland - Alessandro Lania; Ben Pabst; Torsten M. Scheyer (Swiss Journal of Palaeontology)
Abstract Non-sauropodan sauropodomorphs represented the most abundant and diverse herbivore component of the Gondwanan continental paleoecosystems during the Late Triassic. Nonetheless, a constantly increasing diversity has been recovered also from Laurasian formations, such as the Klettgau Formation, which is best exposed at the Gruhalde clay pit (Tonwerke Keller AG) in Frick, Canton Aargau, Switzerland. Despite being renowned for mass-accumulation horizons of the plateosaurid Plateosaurus trossingensis, a new fossiliferous layer was recently discovered above the “Plateosaurus bonebeds”, yielding the holotype of the neotheropod Notatesseraeraptor frickensis as well as several partial articulated skeletons of an unknown sauropodomorph. The complete craniomandibular anatomy of an articulated skull, SMF 13.5.37, belonging to a partial skeleton, SMF 13.5, referred to this new latest Norian sauropodomorph from the Klettgau Formation is here presented. Micro-computed tomography scans (µCT) as well as segmentation techniques were employed in order to examine inaccessible craniodental features of the snout of the specimen under study. The osteological investigation and the anatomical comparison with related taxa unveiled a unique mosaic-like combination of plesiomorphic and apomorphic craniomandibular features, implying that the cranial anatomy of SMF 13.5.37 is transitional between non-massopodan plateosaurian and massopodan sauropodomorph morphologies, similarly to the Argentinian Coloradisaurus brevis from the mid-to-late Norian of the Los Colorados Formation. An intermixed craniomandibular condition is also reflected in the phylogenetic results, which resolve SMF 13.5.37 as a basal massopodan, branching out either at the first or third node of Massopoda, representing the first Laurasian non-sauropodiform massopodan. Even though the evolutionary trend towards a complete massopodan-like architecture needs to be further tested with the study of the postcranium, SMF 13.5.37 unequivocally represents the skull of a new massopodan sauropodomorph taxon from Switzerland, shedding light on a more diversified herbivorous dinosaurian paleofauna from the Norian comparable to those of South America and Africa, as it represents the fourth officially recognized non-sauropodan sauropodomorph along with Plateosaurus trossingensis, Gresslyosaurus ingens and Schleitheimia schutzi.